Developing Digital Skills Trough Blended Learning Activities - Onita-Maria Pavelea; Nicolae Cristian Stan (Babes-Bolyai University, 2023)
The article represents the developing digital skills through blended learning activities.Bibliography was studied for the comparative analysis between blended learning and digital skills. I left the research questions: What is Digital ability? What is mixed learning? What digital application are useful for developing digital skills in preschoolers? How do we develop digital skills through blended learning? We have found that digital skills can be developed through blended learning activities. Blended learning is an educational paradigm, a new way of teaching through the use of digital applications. Digital ability is a necessary to develop through blended learning system, as it brings an additional benefit to the professions of the future.